Characteristics of hyperthermia-induced hyperventilation in humans. Issue 1 (2nd January 2016) - Tsuji, Bun; Hayashi, Keiji; Kondo, Narihiko; Nishiyasu, Takeshi
ABSTRACT: In humans, hyperthermia leads to activation of a set of thermoregulatory responses that includes cutaneous vasodilation and sweating. Hyperthermia also increases ventilation in humans, as is observed in panting dogs, but the physiological significance and characteristics of the hyperventilatory response in humans remain unclear. The relative contribution of respiratory heat loss to total heat loss in a hot environment in humans is small, and this hyperventilation causes a concomitant reduction in arterial CO2 pressure (hypocapnia), which can cause cerebral hypoperfusion. Consequently, hyperventilation in humans may not contribute to the maintenance of physiological homeostasis (i.e., thermoregulation). To gain some insight into the physiological significance of hyperthermia-induced hyperventilation in humans, in this review, we discuss 1) the mechanisms underlying hyperthermia-induced hyperventilation, 2) the factors modulating this response, and 3) the physiological consequences of the response.